Foliar Sprays of Citric Acid and Malic Acid Modify Growth, Flowering, and Root to Shoot Ratio of Gazania (Gazania rigens L.): A Comparative Analysis by ANOVA and Structural Equations Modeling - Majid Talebi; Ebrahim Hadavi; Nima Jaafari (Advances in Agriculture)
Foliar application of two levels of citric acid and malic acid (100 or 300 mg L−1) was investigated on flower stem height, plant height, flower performance and yield indices (fresh yield, dry yield and root to shoot ratio) of Gazania. Distilled water was applied as control treatment. Multivariate analysis revealed that while the experimental treatments had no significant effect on fresh weight and the flower count, the plant dry weight was significantly increased by 300 mg L−1 malic acid. Citric acid at 100 and 300 mg L−1 and 300 mg L−1 malic acid increased the root fresh weight significantly. Both the plant height and peduncle length were significantly increased in all applied levels of citric acid and malic acid. The display time of flowers on the plant increased in all treatments compared to control treatment. The root to shoot ratio was increased significantly in 300 mg L−1 citric acid compared to all other treatments. These findings confirm earlier reports that citric acid and malic acid as environmentally sound chemicals are effective on various aspects of growth and development of crops. Structural equations modeling is used in parallel to ANOVA to conclude the factor effects and the possible path of effects.